Reflexões sobre a utilização do balanced scorecard na gestão da cadeia de suprimentos: um estudo de caso na unidade operacional de uma grande distribuidora de combustíveis - Burmann, Fernanda Nerva (2015)
Contemporary organizations present a high level of complexity. The long process chain shall be managed in an integrated way and requires a decentralized way of decision making in order to assure quick answers to changes in the competitive environment. This context demands the development of management tools to support managers in order to reach global strategic goals as the reference model analyzed in this paper, which gathers supply chain management metrics together with the Balanced Scorecard concept. The aim of this paper is both to evaluate the current Key Performance Indicators (KPIs) architecture of a large fuel distributor company operational unit (OU) based on the reference model and to test, based on a case study, the universality of adopting the reference model by different companies. Some of the main findings of this paper are: the current OU performance indicators architecture is unbalanced according to the BSC dimensions – comparing with the financial dimension that presents 7 KPIs, client dimension presents only 2; the list of OU KPIs presents a gap of 50% compared to the reference model; for this gaps an action plan was built in order to add this indicators to the OU KPIs architecture; 24% of the reference model metrics are not applicable to the OU reality and; the reference model does not cover important items as training, engagement, Health, Safety & Environment (HSE) which are essential to the company context – for instance, the OU currently monitors 6 indicators of HSE. The paper has also found that a generic model is not fully applicable because every organization has its specific complexities. However the reference model can be used as a guidance to verify the adequacy of a specific company preselect indicators because it shows gaps that cannot be detected during the indicators selection process.